Multicentre, randomised clinical trial comparing intravitreal aflibercept monotherapy versus aflibercept combined with reduced-fluence photodynamic therapy (RF-PDT) for the treatment of polypoidal choroidal vasculopathy. Issue 7 (15th July 2021) - Vyas, Chinmayi Himanshuroy; Cheung, Chui Ming Gemmy; Tan, Colin; Chee, Caroline; Wong, Kelly; Jordan-Yu, Janice Marie N.; Wong, Tien Yin; Tan, Anna; Fenner, Beau; Sim, Shaun; Teo, Kelvin Yi Chong
Abstract : Purpose: To compare the efficacy and safety of intravitreal aflibercept (IVA) monotherapy versus aflibercept combined with reduced-fluence photodynamic therapy (RF-PDT) (IVA+RF-PDT) for the treatment of polypoidal choroidal vasculopathy (PCV). Methods and analysis: Multicentred, double-masked, randomised controlled trial to compare the two treatment modalities. The primary outcome of the study is to compare the 52-week visual outcome of IVA versus IVA+RF PDT. One hundred and sixty treatment-naïve patients with macular PCV confirmed on indocyanine green angiography will be recruited from three centres in Singapore. Eligible patients will be randomised (1:1 ratio) into one of the following groups: IVA monotherapy group—aflibercept monotherapy with sham photodynamic therapy (n=80); combination group—aflibercept with RF-PDT (n=80). Following baseline visit, all patients will be monitored at 4 weekly intervals during which disease activity will be assessed based on best-corrected visual acuity (BCVA), ophthalmic examination findings, optical coherence tomography (OCT) and angiography where indicated. Eyes that meet protocol-specified retreatment criteria will receive IVA and sham/RF-PDT according to their randomisation group. Primary endpoint will be assessed as change in BCVA at week 52 from baseline. Secondary endpoints will include anatomical changes based on OCT and dye angiography as well as safety assessment. Additionally, we will be collecting optical coherence tomography angiography data prospectively for exploratory analysis. Ethics and dissemination: This study will be conducted in accordance with the ethical principles that have their origin in the Declaration of Helsinki and that are consistent with the ICH E6 guidelines of Good Clinical Practice and the applicable regulatory requirements. Approval from the SingHealth Centralised Institutional Review Board has been sought prior to commencement of the study. Trial registration number: NCT03941587 .